1968
DOI: 10.1002/ijc.2910030303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reticuloendothelial system stimulation on resistance to rous sarcoma virus infection in chicks

Abstract: By using a non‐toxic reticuloendothelial system stimulant, lipid‐Restim, derived from shark livers, we were able to demonstrate the following effects on growing Rous sarcoma tumors in young chicks. Prechallenge Restim treatment: Significant reduction of the percentage of chicks with tumors and prolongation of the latent period resulted from combined administration of Restim and specific antiserum. Postchallenge Restim treatment: The mortality data indicated that there was a significant increase in survival tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1970
1970
1983
1983

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Male Swiss Webster mice (Blue Spruce Farms, Inc., Altamont, N.Y.), weighing 20 g, were injected intravenously with varying amounts of shark-liver lipid extract, Restim (a non-toxic RES stimulatory agent previously studied at this institute [2,[7][8][9]13]), as an emulsion; or, in a second group of ex periments, with varying dilutions of LPS, prepared as described above. Two days later, the mice were injected intravenously with 800 ug LPS/mousc, prepared as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male Swiss Webster mice (Blue Spruce Farms, Inc., Altamont, N.Y.), weighing 20 g, were injected intravenously with varying amounts of shark-liver lipid extract, Restim (a non-toxic RES stimulatory agent previously studied at this institute [2,[7][8][9]13]), as an emulsion; or, in a second group of ex periments, with varying dilutions of LPS, prepared as described above. Two days later, the mice were injected intravenously with 800 ug LPS/mousc, prepared as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Seven days later, they were injected intravenously with various amounts of a shark-liver lipid extract, Restim (see above), as an emulsion in 5 °/o glucose solution, prepared by the use of procedures previously described [2,9].…”
Section: Rous Sarcoma Virus (Rsv)i Infection In Chicksmentioning
confidence: 99%
“…Some histological evidence that recruitment of cells plays a role in establishing a tumor at the site of RSV inoculation is provided in the studies by Levine (1939) who showed that, following RSV inoculation, a large number of cells invaded the area and that some of these cells may have contributed to tumor formation. However, some evidence has also been presented to show that stimulation of the reticuloendothelial system may play a role in increasing resistance to Rous sarcomas (Bliznakov, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the following substances inhibit primary tumorigenesis: BCG in the MSV-mouse (Schwartz et al, 1971;Houchens et al, 1973), polyoma-hamster and -mouse (Lemonde and Clode-Hyde, 1966), and adenovirus-mouse systems; Freund's complete adjuvant in the adenovirus-mouse system ; thymosin in the MSV-mouse system (Zisblatt et al, 1970); polyribonucleotides (Sarma et al, 1969;Gazdar et al, 1972a;De Clercq and Stewart, 1974) and interferon (Berman, 1970) in the MSV-mouse system; clam liver extract in the adenovirus 12-hamster system (Li et ai., 1972); lipid-restim in the RSV-chicken system (Bliznakov, 1968); rifampicin (Toolan and Ledinko, 1972) and methotrexate (Li et ai., 1972) in the adenovirus-hamster system; cyclophosphamide in the MSV-mouse system, and estrone in the SV40-hamster system (Ohtaki, 1978). Endotoxin (Strausser and Bober, 1972) inhibited the growth of MSV mouse tumors; cyclophosphamide and retinoic acid stimulated CRA activity (Glaser, 1979c) and enhanced activity of the Winn test (Glaser, 1979d;Glaser and Lotan, 1979) in the SV40-mouse system.…”
Section: The Primary In Vivo Systemsmentioning
confidence: 99%